Mediocracy ; The politics of the extreme centre - Deneault, Alain, 1970- (Between the Lines, 2018)
"Medi·oc·racy, noun: the state of domination created by a ruling class composed entirely of mediocre people, for instance, Justin Trudeau, Emmanuel Macron, etc. There was no Reichstag fire. No storming of the Bastille. No mutiny on the Aurora. Instead, the mediocre have seized power without firing a single shot. They rose to power on the tide of an economy where workers produce assembly-line meals without knowing how to cook at home, give customers instructions over the phone that they themselves don't understand, or sell books and newspapers that they never read. Alain Deneault is a writer, philosopher, and academic known for his exposés of off-shore tax havens and mining giants. But now, he delves in to our present-day struggle against a global regime that seeks to extinguish critical thought. Deneault is a Director of the Collège international de philosophie in Paris and is a professor of sociology at the Université de Québec à Montréal. Mediocracy has sold over 50,000 copies in French."--